Online Learning Service Application Using Flutter Framework and Laravel - Yusuf Kurnia (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2022)
Online learning is a concept of learning that is carried out online or through the internet network. Very advanced technology in the modern era and globalization makes various activities carried out efficiently and can be done using only gadgets. Technological developments in the field of education with the use of e-learning in learning activities in schools, colleges, courses and even online communities have started to use concepts like this. This study uses Flutter to create applications for users and consultants in conducting online consultations on android devices. The author uses a collection of widgets that have been provided by flutter to create components in the user interface such as buttons, input text, text, icons, and others. In this study, we use the Laravel framework to create an admin dashboard and provide a Restful API for android applications to handle database management on the server. The author uses Laravel's features to build a fullstack application that handles requests, routing, controllers, services, models, and views.